2022
DOI: 10.3390/nano12020232
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Processing Parameters on the Laser-Ablation of Stainless Steel and Brass during the Engraving by Nanosecond Fiber Laser

Abstract: In this paper, we investigate the influence of the following parameters: pulse duration, pulse repetition rate, line-to-line and pulse-to-pulse overlaps, and scanning strategy on the ablation of AISI 316L steel and CuZn37 brass with a nanosecond, 1064-nm, Yb fiber laser. The results show that the material removal rate (MRR) increases monotonically with pulse duration up to the characteristic repetition rate (f0) where pulse energy and average power are maximal. The maximum MRR is reached at a repetition rate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Tang [ 6 ] fabricated spike-shaped microstructured arrays on brass substrates and obtained superhydrophobic metal surfaces using pulsed ultraviolet (UV) laser ablation. Hribar et al [ 7 ] studied the influence of the processing parameters on the laser-ablation of stainless steel and brass during the engraving by nanosecond fiber laser. Yang et al [ 8 ] confirmed that the surface chemistry is not the only factor to determine surface super-hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…Tang [ 6 ] fabricated spike-shaped microstructured arrays on brass substrates and obtained superhydrophobic metal surfaces using pulsed ultraviolet (UV) laser ablation. Hribar et al [ 7 ] studied the influence of the processing parameters on the laser-ablation of stainless steel and brass during the engraving by nanosecond fiber laser. Yang et al [ 8 ] confirmed that the surface chemistry is not the only factor to determine surface super-hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…Although the process is material-dependent [ 5 ], the study of the main processing parameters that lead to the formation of LIPSS have been identified for various metals, semiconductors and dielectrics [ 1 ], including material properties (optical [ 6 , 7 ], thermal [ 8 ], chemical [ 9 ]), processing conditions (number of effective pulses per spot unit [ 10 , 11 , 12 ], scanning direction vs. polarization [ 13 ], over-scanning [ 14 ], irradiation atmosphere [ 15 ], surface polishing [ 16 ], substrate temperature [ 17 , 18 ], material thickness [ 19 , 20 ]) and laser source parameters (wavelength [ 21 ], pulse duration [ 22 ], beam polarization [ 23 ], angle of incidence [ 24 ], and number of beams [ 25 , 26 ]). Lately, the increasing availability of affordable and stable high-repetition rate femtosecond lasers have been placed under the spotlight, with the laser repetition rate as a key processing parameter to investigate in detail [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. One reason is because materials irradiated at such high rates present heat accumulation effects that can affect dramatically the overall formation and performance of LIPSS [ 32 , 34 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the current level of production development, it is impossible to implement the control of cutting tool manufacturing by laser ablation without fully digitizing the production cycle [1][2][3][4]. Parts with holes are an important part of mechanical engineering.…”
Section: Introductionmentioning
confidence: 99%